PPKM EMERGENCY: GOVERNMENT RESPONSIBILITIES AND NEEDS - Lestari Victoria Sinaga (NOMOI Law Review, 2021)
This research is the government's support to implement law number 6 of 2018 concerning Health Quarantine in preventing the spread of the corona virus in Indonesia.A number of positive corona patients in Indonesia have more than 1000 people, the government needs to take over the mandate so that Emergency PPKM is carried out, namely the Enforcement of Restrictions on Community Activities.Keywords: Government, Restrictions on Community Activities, Quarantine